Significantly Increased Patient Satisfaction Following Liquid Formulation AbobotulinumtoxinA Treatment in Glabellar Lines: FACE-Q Outcomes From a Phase 3 Clinical Trial. (24th September 2019) - Ascher, Benjamin; Rzany, Berthold; Kestemont, Philippe; Hilton, Said; Heckmann, Marc; Bodokh, Isaac; Noah, Ernst Magnus; Boineau, Dominique; Kerscher, Martina; Volteau, Magali; Le Berre, Philippe; Picaut, Philippe
Abstract: Background: The FACE-Q patient-reported outcome assesses patient experiences/outcomes with aesthetic facial procedure. A recent trial of abobotulinumtoxinA (ASI, liquid formulation) was the first to our knowledge to assess satisfaction with FACE-Q after glabellar line (GL) injection. Objectives: The authors sought to evaluate patient satisfaction with ASI for GL treatment employing 3 FACE-Q scales: facial appearance, psychological well-being, and aging appearance. Methods: This was a Phase 3, randomized, double-blind, placebo-controlled trial (NCT02353871) of ASI 50 units in adults with moderate-to-severe GL with 6-month follow-up. Results: Significantly greater least squares mean changes from baseline were associated with ASI treatment (N = 125) vs placebo (N = 59) for satisfaction with facial appearance at all visits until day 148 (5 months; P < 0.0001-0.0037), psychological well-being at all visits ( P < 0.0001-0.0279), and aging appearance at all visits except day 148 ( P < 0.0001-0.0409). Significant differences (ASI vs placebo) were observed at all visits for individual items: "how rested your face looks" ( P < 0.0001-0.0415), "I feel okay about myself" ( P = 0.0011-0.0399), and "I feel attractive" ( P < 0.0001-0.0102). Maximal least squares mean (standard error) changes in aging appearance score were −1.4 (0.3; ASI) and −0.3 (0.4; placebo). Investigators' live assessment of GL at maximum frown significantly correlated with improvements in FACE-Q facial appearance and psychological scales (all patients: r = −0.41 and r = −0.36 [both P < 0.0001], respectively). Conclusions: Significant improvements in patient satisfaction with aging, facial appearance, and, importantly, psychological well-being were demonstrated with ASI employing FACE-Q scales up to 5 to 6 months post-injection. Results support a long duration of efficacy with ASI and use of FACE-Q in future trials and clinical practice. Level of Evidence: 1: